The reproduction of second-hand apparel shopping : understanding second-hand apparel consumption from a practice-based approach - Fröding, Alexandra (SLU/Dept. of Urban and Rural Development, 2017)
Textile and apparel consumption highly affect the environment, and a large amount of useable clothes are disposed to trash. This study examines second-hand shopping of clothes from a practice-based approach, more specifically Shove et al.'s (2012) view of practice theory, to create an understanding of how the practice is constituted and reproduced by its members. Data were collected through seven in-depth, semi-structured interviews with individuals involved in second-hand shopping. The analysis showed different links between the elements of meanings, materials and competences. Meanings are for example aspirations to live sustainably, from being unique to being sustainable, and enjoyment and positive feelings. Materials that are part of the practice are physical barriers, low prices and a vast supply. Competences related to the practice are the view on it as part of life, the skill of navigating the vast supply, and the skill of being patient. The analysis further showed that the practice is vivid, constantly changing and reproduced by its carriers, and that second-hand shopping incorporates reflection of the overall way of life. The study contributes to an understanding of one specific sustainable practice and these insights can further be helpful in preventing unsustainable shopping practices.